Le fiduciaire doit-il désintéresser les tiers créanciers privilégiés? - Demers, Robert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
What, if any, are the trustee for bondholder's obligations when proceeding with the sale of a debtor's property ? Section 30 of the Special Corporate Powers Act is silent on the question of third party creditors in such a situation. Must we necessarily conclude for that reason that the trustee is not obliged to disinterest privileged claims ranking above his according to the rule of C.C. article 1994 ? This paper deals with this controversial subject. More than seventy years of provincial case-law has affirmed this duty while not being very precise as to its foundation. The general principles of civil law perhaps can indicate what would be the explanation for such a rule while giving an interesting point of view on what constitutes a privilege.